Sposób filozofowania Mikołaja Bierdiajewa jako skutek jego rozumienia twórczości i wolności - Kashchuk, Vitaliy (Warszawskie Studia Teologiczne, 2017)
Studying the work of this or that thinker, his or her topics of interest, the form of expressing his or her ideas, the direction of research, conclusions, in some cases, one can see some dependence between the author’s approach to life, which manifests itself in various domains, and his or her philosophy.Similarly when we take into consideration academic achievements of N. Berdyaev, and, particularly his essential philosophical topics such as freedom and creativity, and to be exact the work as a result of freedom, it is impossible not to notice some kind of connection between the issues raised by the philosopher and his own style of philosophizing, namely the form, the way of expression and his language.This article is an attempt to look at how N. Berdyaev understood freedom, what he expected of the creativity and whether he fulfilled his personal thoughts in his manner of philosophizing.